PERSEPSI SISWA TERHADAP PENERAPAN TATA TERTIB SEKOLAH DI SMP ISLAM AL-AZHAR 57 JAMBI - Fanisa, Fanisa Nurul Azizah; Try Susanti; Yusrotul Aini; Fathurrahman Rizky; Indra Solihin; Tiara Nova Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to explore students’ perceptions of the implementation of school rules at SMP Islam Al-Azhar 57 Jambi. The research is motivated by the importance of school regulations in maintaining order and creating a conducive learning environment, while also addressing various behavioral challenges among adolescents. The study employed a descriptive qualitative approach, involving students who had direct experience with the application of school rules. The findings indicate that most students consider the rules to be clearly formulated, easy to understand, and consistently enforced by teachers. However, students’ compliance varies, particularly regarding dress code regulations such as wearing headscarves, the length of socks, and haircut requirements, which some students find uncomfortable. Despite certain rules being perceived as strict, students acknowledge the benefits of school regulations, as they encourage discipline and contribute to a more orderly learning environment. Most students believe the existing rules are appropriate, with only a few suggesting minor adjustments. Overall, the implementation of school rules is considered effective, though further efforts are needed to strengthen students’ sense of responsibility to ensure optimal adherence. Keyword: Perception, Students, School Rules, Discipline